Emotional regulation and the occurrence and course of hypertension - Małgorzata Agnieszka Piotrowska-Półrolnik; Izabela Krejtz; Paweł Holas (Journal of Education, Health and Sport, 2017)
This article aims to draw attention to the role of psychological factors in morbidity, progression, as well as in the treatment of hypertension. Psychological factors, especially how a person regulates negative emotions, can contribute to the increased risk of cardiovascular disease or exacerbation of these diseases.